Poets on place: tales and interviews from the road - Pfefferle, W. T., author; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Out to see America and satisfy his travel bug, W.T. Pfefferle resigned from his position as director of the writing program at Johns Hopkins University and hit the road to interview sixty-two poets about the significance of place in their work. The lively conversations that resulted may surprise with the potential meanings of a seemingly simple concept. This gathering of voices and ideas is illustrated with photo and word portraits from the road and represented with suitable poems. The poets are James Harms, David Citino, Martha Collins, Linda Gregerson, Richard Tillinghast, Orlando Ricardo Menes, Mark Strand, Karen Volkman, Lisa Samuels, Marvin Bell, Michael Dennis Browne, David Allan Evans, David Romtvedt, Sandra Alcosser, Robert Wrigley, Nance Van Winckel, Christopher Howell, Mark Halperin, Jana Harris, Sam Hamill, Barbara Drake, Floyd Skloot, Ralph Angel, Carol Muske-Dukes, David St. John, Sharon Bryan, Donald Revell, Claudia Keelan, Alberto Rios, Richard Shelton, Jane Miller, William Wenthe, Naomi Shihab Nye, Peter Cooley, Miller Williams, Beth Ann Fennelly, Natasha Trethewey, Denise Duhamel, Campbell McGrath, Terrance Hayes, Alan Shapiro, Nikki Giovanni, Charles Wright, Rita Dove, Henry Taylor, Dave Smith, Nicole Cooley, David Lehman, Lucie Brock-Broido, Michael S. Harper, C.D. Wright, Mark Wunderlich, James Cummins, Frederick Smock, Mark Jarman, Carl Phillips, Scott Cairns, Elizabeth Dodd, Jonathan Holden, Bin Ramke, Kenneth Brewer, and Paisley Rekdal.
Wherein We Begin Life on the Road -- James Harms - Morgantown, West Virginia -- Landscape as the Latest Diet (Southern California) / James Harms -- David Citino - Columbus, Ohio -- Through a Glass, Darkly / David Citino -- Martha Collins - Oberlin, Ohio -- Linda Gregerson - Ann Arbor, Michigan -- Richard Tillinghast: Ann Arbor, Michigan -- Wake Me in South Galway / Richard Tillinghast -- Winnie Cooper -- Orlando Ricardo Menes - South Bend, Indiana -- Mark Strand - Chicago, Illinois -- A Morning / Mark Strand -- Karen Volkman - Chicago, Illinois -- Lisa Samuels - Milwaukee, Wisconsin -- Marvin Bell - Iowa City, Iowa -- Port Townsend, Washington, Waterside -- Dust, Corn, and Popcorn People -- Michael Dennis Browne - Minneapolis, Minnesota -- from At the Cabin / Michael Dennis Browne -- David Allan Evans - Brookings, South Dakota -- David Romtvedt - Buffalo, Wyoming -- With Caitlin, Age 8, Building a Qhuinzee for a Winter Night / David Romtvedt -- The West -- Sandra Alcosser - Lolo, Montana -- Mare Frigoris / Sandra Alcosser -- Robert Wrigley - Moscow, Idaho -- Ordinary Magic / Robert Wrigley -- Nance Van Winckel - Liberty Lake, Washington -- Awaiting the Return Ferry / Nance Van Winckel -- Christopher Howell - Spokane, Washington -- Wherein the Author Ruminates on RV Life -- Mark Halperin - Ellensburg, Washington -- Accident / Mark Halperin -- Jana Harris - Sultan, Washington -- Mr. Elija Welch, First Planting / Jana Harris -- Sam Hamill - Port Townsend, Washington -- The Day I Did Winnie Cooper Wrong -- Barbara Drake - Yamhill, Oregon -- from The Man from the Past Visits the Present / Barbara Drake -- Floyd Skloot - Amity, Oregon -- A Warming Trend / Floyd Skloot -- Suddenly in California -- Ralph Angel - South Pasadena, California -- Carol Muske-Dukes - Los Angeles, California -- Twin Cities / Carol Muske-Dukes -- David St. John - Venice, California -- Dijon / David St. John -- Sharon Bryan - San Diego, California -- Death Valley -- Donald Revell & Claudia Keelan - Las Vegas, Nevada -- A Parish in the Bronx / Donald Revell -- Alberto Rios - Chandler, Arizona -- Richard Shelton - Tucson, Arizona -- Local Knowledge / Richard Shelton -- Jane Miller - Tucson, Arizona -- #15 from A Palace of Pearls / Jane Miller -- New Year -- William Wenthe - Lubbock, Texas -- Alien / William Wenthe -- Naomi Shihab Nye - San Antonio, Texas -- Pause / Naomi Shihab Nye -- Peter Cooley - Jefferson, Louisiana -- Miller Williams - Fayetteville, Arkansas -- RV Life 2 -- Beth Ann Fennelly - Oxford, Mississippi -- from The Kudzu Chronicles / Beth Ann Fennelly -- Natasha Trethewey - Decatur, Georgia -- South / Natasha Trethewey -- Denise Duhamel - Hollywood, Florida -- Valentines, Hollywood Beach / Denise Duhamel -- Campbell McGrath - Miami Beach, Florida -- Terrance Hayes - Columbia, South Carolina -- Threshold / Terrance Hayes -- Alan Shapiro - Chapel Hill, North Carolina -- Bower / Alan Shapiro -- Nikki Giovanni - Blacksburg, Virginia -- Charles Wright - Charlottesville, Virginia -- High Country Spring / Charles Wright -- Choosing -- Rita Dove - Charlottesville, Virginia -- The House on Bishop Street / Rita Dove -- Henry Taylor - Bethesda, Maryland -- Harvest / Henry Taylor -- Dave Smith - Baltimore, Maryland -- Gaines Mill Battlefield / Dave Smith -- Nicole Cooley - Glen Ridge, New Jersey -- Unfinished Sketch: Green Sandbox Winter Sky / Nicole Cooley -- David Lehman - New York, New York -- April 9 / David Lehman -- The City So Nice They Named It Twice -- Lucie Brock-Broido - New York, New York -- Michael S. Harper - Providence, Rhode Island -- C. D. Wright - Barrington, Rhode Island -- from The Ozark Odes / C. D. Wright -- Mark Wunderlich - Provincetown, Massachusetts -- Elevation -- James Cummins - Cincinnati, Ohio -- Spring Comes to Hamilton Avenue / James Cummins -- Frederick Smock - Louisville, Kentucky -- Heron / Frederick Smock -- Mark Jarman - Nashville, Tennessee -- Nashville Moon / Mark Jarman -- Carl Phillips - St. Louis, Missouri -- Driveway -- Scott Cairns - Columbia, Missouri -- Mud Trail / Scott Cairns -- Elizabeth Dodd - Manhattan, Kansas -- Sonnet, Almost / Elizabeth Dodd -- Jonathan Holden - Manhattan, Kansas -- Pigs -- Bin Ramke - Denver, Colorado -- Kenneth Brewer - Logan, Utah -- Paisley Rekdal - Salt Lake City, Utah -- Ode / Paisley Rekdal -- Wherein the Author Considers the End -- Gas Giant
Keywords: American poetry -- 20th century -- History and criticism -- Theory, etc.; American poetry -- 21st century -- History and criticism -- Theory, etc.; Poets, American -- 20th century -- Interviews; Poets, American -- 21st century -- Interviews; Place (Philosophy) in literature; Regionalism in literature; Local color in literature; Setting (Literature); United States -- Description and travel; United States -- In literature; Pfefferle, W. T. -- Travel -- United States